Incivility and danger: theorizing a Muslim undercaste in Europe - Becker-Topkara, Elisabeth (American journal of cultural sociology, 2022)
Positing Muslim positionality in Europe as an undercaste helps to make sense of how cultural stratification, rooted in associations with incivility, has resulted in deep and unrelenting inequalities experienced by diverse Muslims. Based on two years of ethnographic research with a Muslim community in Berlin as well as a survey of secondary research, this paper both theorizes and empirically showcases the process by which Muslims have become synonymous with incivility, and how this affects opportunities and inclusion across the educational, economic, residential, and private spheres. By drawing parallels with other instances of caste-based status differentiation in the West, specifically the Jewish experience in Europe and Black experience in the USA, it further illuminates how cultural stratification through associations with incivility (as a modern secular coding of impurity) that endures for generations functions in the contemporary world. Employing the concept of caste deepens the cultural turn that has replaced economic or legal explanations of Muslim marginality in Europe. And it awakens a dormant sociological vocabulary that allows for a more precise theoretical understanding of this empirical social phenomenon and thereby the possibilities—and limits—of pluralism in modernity.
Gesehen am 11.04.2023